PENGARUH KUALITAS LABA PADA YIELDS OBLIGASI DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI - ELIADA HERWIYANTI; ZAKI BARIDWAN (Jurnal Bisnis dan Akuntansi, 2008)
The objective of this research is to study the effect of earnings quality to bond yields, and whether the effect of earnings quality to bond yields can be moderated by corporate governance. In this paper, earnings quality was proxied by discretionary accruals. Yield to maturity approximation was used to count the bond yields. The proxies of corporate governance are institutional ownership and outside director. This research is using purposive sampling method to choose the sample. From six years observation period, 153 observation bonds obtained. To test the hypothesis, this research using logistic regression. This research indicated that model of logistic regression is fit, although the result for hypothesis examination not significant. The lowest Nagelkerke’s R2 value indicated that other variables which not include in this research may have contribution for the research model. Result of this research could be happened because of the naive behavior from investor it-self, the characteristic of bond market, less familiarity of corporate governance regulation, or may be from the lack of variable used in the research model.